Decision-Making in Light of The Prophetic Hadith - Klaina, Mekki (TAJDID, 2024)
This research delves into the principles of decision-making within the Islamic vision, contrasting these with Western perspectives to highlight the unique approach Islam takes towards ethical decision-making and governance. The study emphasizes the role of morality and communal welfare in Islamic decision-making, aspects that are sometimes less emphasized in Western models, which often focus on efficiency and profitability. Utilizing a methodological analysis of primary Islamic texts, including the Quran and Hadith, alongside a review of secondary sources, the research identifies key attributes of Islamic decision-making processes. These include the emphasis on consultative processes and the integration of ethical and moral considerations into decision-making practices. Findings from the study suggest that Islamic decision-making not only considers the outcomes but also the ethical means to achieve them, promoting a holistic approach to leadership and management. The research opens pathways for integrating Islamic principles into contemporary management and governance practices, potentially enriching global management strategies with deeper ethical considerations. This comparative analysis invites further exploration into how these principles can be operationalized in modern organizational settings, suggesting a broader applicability of Islamic ethics in addressing contemporary management challenges.